Flies : the natural history & diversity of Diptera - Marshall, S. A. (Stephen A.) (Richmond Hill, Ont. : Firefly Books, 2012)
"Meticulously researched and illustrated with more than 2000 color photographs taken by the author, Flies is a landmark reference book that will be indispensable to any naturalist, biologist or entomologist. Most photographs in this encyclopedic reference were taken in the field and show the insects in their natural environment. All of the world's fly families are included, with photographic coverage spanning the range from common deer flies and fruit flies through to deadly tsetse flies and malaria mosquitoes, with thousands of spectacular species such as exotic stalk eyed flies, giant robber flies and hedgehog flies in between. Flies is broken up into three parts: Life Histories, Habits and Habitats of Flies; Diversity; and Identifying and Studying Flies. The 20 pages of profusely illustrated keys linked to the unprecedented photographic coverage of the world's fly families and subfamilies enable the reader to identify most flies quickly and accurately, and to readily access information about each family as well as hundreds of distinctive genera and species"--Publisher's description.
Introduction: The dominance of Diptera -- pt. 1. Life histories, habits and habitats of flies. Life histories of flies ; Flies, plants and fungi ; Flies and vertebrates ; Flies and invertebrates -- pt. 2. Diversity. Origins & distribution of the Diptera ; The lower Diptera ; The lower Brachycera and Empidoidea ; The higher Brachycera or Cyclorrhapha -- pt. 3. Identifying and studying flies. Collecting and preserving flies ; Identifying flies -- General glossary and commentary on taxonomic terminology.
Includes bibliographical references and index.
Keywords: Diptera; Flies; Mouches; Diptera; Flies; Systematik; Flugor